Histone hyperacetylation within the β-globin locus is context-dependent and precedes high-level gene expression - Fromm, George (American Society of Hematology, 2009)
Active gene promoters are associated with covalent histone modifications, such as hyperacetylation, which can modulate chromatin structure and stabilize binding of transcription factors that recognize these modifications. At the β-globin locus and several other loci, however, histone hyperacetylation extends beyond the promoter, over tens of kilobases; we term such patterns of histone modifications “hyperacetylated domains.” Little is known of either the mechanism by which these domains form or their function. Here, we show that domain formation within the murine β-globin locus occurs before either high-level gene expression or erythroid commitment. Analysis of β-globin alleles harboring deletions of promoters or the locus control region demonstrates that these sequences are not required for domain formation, suggesting the existence of additional regulatory sequences within the locus. Deletion of embryonic globin gene promoters, however, resulted in the formation of a hyperacetylated domain over these genes in definitive erythroid cells, where they are otherwise inactive. Finally, sequences within β-globin domains exhibit hyperacetylation in a context-dependent manner, and domains are maintained when transcriptional elongation is inhibited. These data narrow the range of possible mechanisms by which hyperacetylated domains form.